SELF-REPORTED HALITOSIS AND ASSOCIATED FACTORS AMONG THE ELDERLY - Abdat, Munifah; Andriany, Poppy; Novita, Cut Fera; Herwanda, . (E-Jurnal Medika Udayana; Vol 14 No 6 (2025): E-Jurnal Medika Udayana, 2025)
Halitosis is a common complaint in society. Studies report that about 30% to 50% of the population has experienced halitosis problems. Halitosis is a disturbing problem for many people around the world that affects people's social interactions in everyday life by causing personal discomfort and emotional stress. Caries, periodontal disease, and xerostomia, which are factors associated with halitosis, are common diseases found in the elderly. This study aims to analysis of self-reported halitosis and associated factors among the elderly. This research is a quanitative research. The type of data used is primary data obtained from the results of filling out questionnaires on the elderly and halitosis examinations using organoleptic methods on 35 subjects. The collected data was then analyzed using the t-test and chi-square.The results showed that Halitosis with moderate to very strong odor is experienced by 91.5% of elderly. Factors related to halitosis are still many root remains, cavities, plaque disease, calculus, gingivitis, disease, hyposalivation periodontal tissue, coated tongue. There is no significant relationship between gender, calculus, periodontal disease, hyposalivation, and coated tongue with the degree of halitosis. It can be concluded that the personal perception of the elderly regarding the halitosis they experience is still low, even though they suffer from halitosis moderate to very strong odor.